Symulacja dynamiki drzewostanów sosnowych polskiej i ukraińskiej części Roztocza w warunkach zmian klimatu - Kozak, Ihor; Czekajska, Patrycja; Kociuba, Piotr; Kozak, Hanna; Stępień, Adam (Leśne Prace Badawcze, 2013)
The study was conducted in the Polish (Roztoczanski National Park) and Ukrainian (Rava-Rus’ka Landscape Reserve and Yavorivskyi National Park) parts of the Roztocze region. In each of these locations three research areas were established in Scots pine ( Pinus sylvestris L.) stands under similar ecological conditions. The purpose of this study was to carry out a survey of possible scenarios for pine stand dynamics in the Polish and Ukrainian parts of Roztocze using the FORKOME model. A control scenario was compared with four other climate change scenarios (warm dry and warm humid; cold dry and cold humid) for a period of covering the next 100 years. Using the control scenario, the FORKOME model predicted that for the next 100 years pine stands will dominate in terms of biomass and number of trees. The warm-dry and warm-humid climate scenarios resulted in slightly reduced biomass of pine stands. However pine would still maintain its dominance, although with a noticeable increase in beech and fir biomass. Nevertheless, in term of the number of trees during the second half of the simulation, it is beech and fir that dominate stand 1 in Roztoczanski National Park. Under the climate cooling scenario (cold dry and cold humid), the biomass of pine and spruce would increase during the next 100 years. Pine trees that would dominate in terms of their numbers, although the number of spruce individuals also tends to increase. The results presented in the paper indicate that the FORKOME model is very useful when investigating different climate changes scenarios in the Roztocze region.